Preparation, Characterization and Cytotoxic Studies of Cisplatin-containing Nanoliposomes on Breast Cancer Cell Lines - Mohammadinezhad, Fateme; Talebi, Armin; Allahyartorkaman, Mohammadreza; Nahavandi, Reza; Vesal, Maryam; Akbarzadeh Khiyavi, Azim; Jabbari Velisdeh, Zeinab; Saberian, Elham; Mirmoghaddam, Paniz; Eslami, Somayeh; Ghanbarikondor, Parizad; Sedighi, Armin; et al. (Asian Pacific Journal of Cancer Biology, 2023)
Objective: Today, cancer is one the most important challenges in modern medicine. Breast carcinoma is one type of cancer that is treated with cisplatin, a chemotherapy drug. By using liposomal nanocarriers, this study seeks to increase the therapeutic efficiency of cisplatin. Method: The zeta potential, particle size, and drug-release characteristics of nanoliposomal cisplatin were evaluated after it had been synthesized using the reverse phase evaporation technique. The cytotoxicity rate of nanoliposomal cisplatin was then assessed using the T-47D breast cancer cell line. Results: This study’s liposomal nanoparticles (NPs) had a zeta potential of -24.9 mV and a particle size of 342.3 nm. 3.51% and 79.6%, respectively, were found to be the drug loading level and amount of encapsulated drug. A significant improvement over the free drug was seen in this nanoliposome’s cytotoxic effect on the T-47D breast cancer cell line (P<0.05). Conclusion: According to what we have discovered, cisplatin liposomal nanocarriers may prove to be a cutting-edge chemotherapy treatment for breast cancer.